مأساة الجسد الذكوريّ في شعر بلند الحيدري - مصطفى علي, طاهر (Al-Adab Journal, 2018)
This research is a study of literary epistemology of the Kurdish and the famous Iraqi poet, Blnd El-Haidery’s poems. The purpose is to appoint a lot of images concerning tragedya of tortured human’s body so as to incarnate this sort of poetic images and their style of drawing which is known as a living style – formerly was called the style of realism. It is composed of combination and compound of literary and the ordinary phenomena of life. Also, reading the images is to search the spirit of poetic and literary aesthetic in them. Actually, they are the output of a great Iraqi contemporary poet who devoted all his life and his art to serve his country and humanity, and also to encounter exploitation and torturing Iraqi human and humanity in general. According to the number of the images, the research consists of eight topics, in addition to an introduction, conclusion and a list of references.